IDENTIFICATION OF CHEMICAL COMPOUNDS OF 70% ETHANOL EXTRACT OF CEMCEM LEAF IN DENPASAR CITY - Adresya, I Gede Bagas Upaditha; Dharmayudha, Anak Agung Gde Oka; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2023)
Traditional medicine is a national cultural heritage that needs to be preserved and developed to support health, one of which is the cemcem ( Spondias pinnata (L.f) Kurz ) plant whose leaves are used. This study aims to determine the class of chemical compounds contained in the ethanol extract of cemcem leaves. The sample used in this study was cemcem leaves obtained in the Denpasar City area, Bali. Cemcem leaves were first extracted using 70% ethanol solvent, then a phytochemical test was carried out to detect the presence of active compounds of alkaloids, flavonoids, saponins, phenolics, triterpenoids/steroids, and tannins. After the data is obtained then analyzed descriptively qualitatively. The results showed that the ethanol extract of cemcem leaves contains alkaloids, flavonoids, saponins, phenolics, triterpenoids/steroids, and tannins. The 70% ethanol extract of cemcem leaves grown in Denpasar City positively contains alkaloids, flavonoids, saponins, tannins, phenolics, and triterpenoids/steroids. This research is an early stage to detect the content of secondary metabolites of alkaloids, flavonoids, saponins, phenolics, triterpenoids/steroids, and tannins, therefore it is necessary to carry out further research on cemcem leaves, for example fractionation so that later it can be applied in the field of veterinary science.